Science and Technology in Manufacture of Oyster Mushroom Seedlings - Hastuti, Liana Dwi Sri; Yurnaliza, Yurnaliza; Fauzi, Fachri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Oyster mushrooms (Pleurotus ostreatus) currently are in high demand because of their good taste and very high protein content. This nutritious and healthy food source make oyster mushrooms a preferable commodity in meeting food needs. It can be marked by the growing demand for oyster mushrooms while oyster mushroom production has not been able to meet the needs of the market, especially mushroom farmers in North Sumatra began to go from just farming by starting from a baglog that was ready to harvest, to providing its own seedlings. Farmers are expected to be able to produce initial seeds directly from fresh mushrooms that have commercial values. This program provides knowledge to farmers on how to develop seeds from fresh mushrooms to produce F-0, F-1, F-2 F-3 and finally baglog. Socialization, live demonstrations and interviews have been conducted by the team. Techniques for obtaining good seedlings by working with aseptic culture techniques and sterilization of growing media have also been given briefly to farmers. This program is expected that farmers have skills in producing seeds with subculture methods, as well as gain knowledge on using sterilization and aseptic techniques to be able to produce good and quality seeds.